The Guiding Principles and the Responsibility to Protect - Erin Mooney (Forced Migration Review, 2008)
At the GP10 conference, several speakers invoked the‘responsibility to protect’ and recommended closely linkingit to the Guiding Principles and with the fate and situationof the millions of IDPs. What might making this connectionbring, conceptually and concretely, to the protection of IDPs?